Analysis of the Role of Job Satisfaction in Improving the Performance of Educators at SMK Maarif NU 2 Karanglewas - Rahmadini Mulya Aisah; Astuti Astuti; Prisilia Mutiara Sari; Eli Indriastuti (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze in depth the role of job satisfaction in improving the performance of educators at SMK Maarif NU 2 Karanglewas. The urgency of this research is based on the fact that the quality of education is highly influenced by teachers’ professionalism, which is inseparable from their psychological condition and satisfaction in carrying out their duties. Job satisfaction is one of the key factors that can affect teachers’ enthusiasm, responsibility, and the quality of educational services provided to students. Therefore, this research seeks to explain how the level of teachers’ job satisfaction contributes to their performance in conducting the teaching and learning process. This study employs a quantitative approach with an ex post facto correlational design to determine the direction and magnitude of the contribution of job satisfaction toward improving teacher performance. The research population consisted of 60 teachers, all of whom were selected using a saturated sampling technique. The research instrument was a Likert-scale questionnaire (1–5) that had passed both construct validity and reliability testing, ensuring accurate data collection. The results revealed that job satisfaction has a positive and significant effect on teacher performance, contributing 38%, while the remaining 62% is influenced by other factors such as work environment, workload, facility availability, and managerial support. Based on these findings, it can be concluded that the higher the level of job satisfaction experienced by teachers, the better their performance in the learning process. Therefore, schools need to pay attention to aspects such as welfare, career development, and a conducive work climate to maintain and improve teachers’ job satisfaction sustainably. Keywords: Job satisfaction, Teacher performance, Vocational high school, Educator productivity